(untitled) (Proceedings of the International Conference on Education, 2019)
Cooperative learning has long been introduced in classroom teaching due to its ability to capitalise on students’ academic and social learning experiences. Having identified the different learning styles and needs of the current student who are the Generation Z (Gen Z) in our classroom, it is crucial to address the question of how applicable is cooperative learning in promoting interactive and effective learning for more rewarding learning experience. This action research attempts to understand the students’ perceptions towards the three cooperative learning strategies they have experienced with the objective to identify the best strategy to enhance the students’ learning experiences. The study population of this action research is the second and third year undergraduates of a compulsory subject. A descriptive research design using a structured questionnaire was used and cooperative learning was found to be an effective approach in enriching the learning experience among the Gen Z learners.